2(x-6)=24-6(x+2)

Simple and best practice solution for 2(x-6)=24-6(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-6)=24-6(x+2) equation:


Simplifying
2(x + -6) = 24 + -6(x + 2)

Reorder the terms:
2(-6 + x) = 24 + -6(x + 2)
(-6 * 2 + x * 2) = 24 + -6(x + 2)
(-12 + 2x) = 24 + -6(x + 2)

Reorder the terms:
-12 + 2x = 24 + -6(2 + x)
-12 + 2x = 24 + (2 * -6 + x * -6)
-12 + 2x = 24 + (-12 + -6x)

Combine like terms: 24 + -12 = 12
-12 + 2x = 12 + -6x

Solving
-12 + 2x = 12 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-12 + 2x + 6x = 12 + -6x + 6x

Combine like terms: 2x + 6x = 8x
-12 + 8x = 12 + -6x + 6x

Combine like terms: -6x + 6x = 0
-12 + 8x = 12 + 0
-12 + 8x = 12

Add '12' to each side of the equation.
-12 + 12 + 8x = 12 + 12

Combine like terms: -12 + 12 = 0
0 + 8x = 12 + 12
8x = 12 + 12

Combine like terms: 12 + 12 = 24
8x = 24

Divide each side by '8'.
x = 3

Simplifying
x = 3

See similar equations:

| -24=-v/4 | | 4(7s+3)-3(6s+4)= | | 3x+4(5x-6)=(38) | | x^2-4y^2+2x+8y-31=0 | | c/12=15 | | (-2x+10)+(-8x-1)=10x+-9 | | w/5=-30 | | 10x-10=55 | | 3x^2-30=-9x | | 8n+3n= | | 1/4y=20 | | -(6x-1)+6x=11 | | x=140+1.3y | | 56=5u-14 | | 3x-4y=420 | | 141.5512=2*3.14*r*7.5+2*3.14*r^2 | | 35=-2x-15-3x | | 15x-20000=24000 | | -10x(x-5)=-8(x+9) | | 2=-9+w | | 13+(5a+3)= | | 2(9-1)-5a=7 | | 3x-4x=420 | | 45x^2+94x+48=0 | | ax-w=3forw | | 7x=9(2+x) | | 1x+500=1200 | | 7x+150=15x | | 34=2v+10 | | 48-3n^2=0 | | .9*.3= | | u/3-13=30 |

Equations solver categories